Parents’ stress level at Neonatal Intensive Care Unit Hospital USM - Joo, Lim Chien
Medically fragile infants are born into families regardless of races, religious, cultural background, socio economical status and nationality. The undesirable and unexpected event of having own child admitted to Neonatal Intensive Care Unit (NICU) causes stress to parents that is characterized by uncertainty and fear. This study aims to assess the level of stress among parent whose infant admitted to NICU and factors contributing to parental stress. A cross-sectional, descriptive study was conducted in 104 respondents whose infant admitted to NICU Hospital Universiti Sains Malaysia using convenience sampling method. Respondents were surveyed using a structured self-administered questionnaire. The questionnaire consisted 26 questions and respondents evaluated each questions on a five- point Likert scale. Data were analyzed using IBM SPSS Statistics version 20.0. Chi- Square test and Fisher’s Exact Test were used to analyze the data. A p-value of equal or less than 0.05 was considered significant. 104 respondents participated in this study. Respondents generally reported low (60.6%) to moderate (36.5%) level of stress when their infant admitted to NICU. Mothers perceived higher level of stress than fathers when their child admitted to NICU by showing significant difference with p-value of 0.002. Although there was no significant association between educational level and overall stress of parents (p= 0.280), there was significant mean difference between educational level and parental stress on subscales of infant appearance and behavior (p= 0.010). On the other hand, there was no significant association between gestational age and stress experienced by parents of infant admitted to NICU with p-value 0.204. There was also no significant difference between length of stay and stress of parents when their infant admitted to NICU (p= 0.180). The results warrant a need to increase awareness of health care providers especially for nurses towards stress of parents. Health care professionals must be attuned to individual differences of parents and be alert of likelihood for gender differences in stress responses between fathers and mothers. Good communication skill is also important as effective communication helps to relieve parental stress, too. It is essential to remove sources of parental stress that ultimately impaired parent infant bonding and lead to child vulnerability in future.